2006
DOI: 10.1007/s00467-006-0257-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia and gout following pediatric renal transplantation

Abstract: Hyperuricemia and gout are common complications in adult renal transplant recipients. In pediatric recipients, however, hyperuricemia seems to be rare, but data are scarce. Thirty-two children (21 males, 11 females) were investigated for a median time of 4.8 years (range: 0.4-11.2 years) following renal transplantation. The median age of this pediatric study group was 13.9 years (range: 5.7-20.3 years), and the calculated glomerular filtration rate (GFR) was 61 ml/min per 1.73 m(2) (range:12-88 ml/min per 1.73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…15 In 1 study with 32 pediatric renal transplant recipients, the prevalence of hyperuricemia was reported as being 47%; the authors did not find any difference of hyperuricemia rate according to different calcineurin inhibitors. 8 In this study, our group was larger, and we found that 39% of patients on cyclosporine and 16% of patients on tacrolimus had hyperuricemia. The rate of hyperuricemia was greater in those patients receiving cyclosporine; however, the patients on cyclosporine had lower estimated glomerular filtration rates and longer transplant durations compared with the patients receiving tacrolimus.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…15 In 1 study with 32 pediatric renal transplant recipients, the prevalence of hyperuricemia was reported as being 47%; the authors did not find any difference of hyperuricemia rate according to different calcineurin inhibitors. 8 In this study, our group was larger, and we found that 39% of patients on cyclosporine and 16% of patients on tacrolimus had hyperuricemia. The rate of hyperuricemia was greater in those patients receiving cyclosporine; however, the patients on cyclosporine had lower estimated glomerular filtration rates and longer transplant durations compared with the patients receiving tacrolimus.…”
Section: Discussionmentioning
confidence: 58%
“…9 Estimated glomerular filtration rate was calculated according to the Schwartz formula with cystatin C. 10 The upper limits of serum UA levels were regarded as 352, 339, and 416 μmol/L in children aged 2 to 15 years in both sexes. 8 The blood pressure of each patient was measured at each follow-up visit. Hypertension was defined as the average systolic blood pressure or diastolic blood pressure ≥ 95th percentile for sex, age, and height on at least 3 separate occasions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In most studies, serum uric acid level was a marker of renal dysfunction. [2][3][4][5][6] However, hyperuricemia occurs early after transplant and is associated with use of diuretics, cyclosporine therapy, a history of hyperuricemia, and decreased glomerular filtration rate (GFR).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In most studies, serum uric acid level was a marker of renal dysfunction. [2][3][4][5][6] However, hyperuricemia occurs early after transplant and is associated with use of diuretics, cyclosporine therapy, a history of hyperuricemia, and decreased glomerular filtration rate (GFR). 1,3,5,7,8 The effect of hyperuricemia after kidney transplant on graft outcome has not been fully established, but a small number of studies have suggested that an increased serum uric acid level is a prognostic factor for the development of renal allograft impairment.…”
Section: Introductionmentioning
confidence: 99%